Synthesis of Caffeic Acid Phenethyl Ester Analogues and Their Cytotoxicities Against Human Cancer Cells - Wang, Yan-Hui; Li, Qu-Sheng; Wang, Peng-Long; Xu, Kuo; Cheng, Ya-Tao; Xu, Xin; Li, Qiang; Zhang, Yu-Zhong; Lei, Hai-Min (Asian Journal of Chemistry, 2014)
Although caffeic acid phenethyl ester exhibits strong antitumor property, but its pharmacophore has not been elaborated clearly as yet. Seventeen caffeic acid phenethyl ester analogues were synthesized via simple and easy procedures and their antiproliferative effects were evaluated toward Bel-7402 and MCF-7 cancer cell lines. Compared to compounds 1-11, 12, 13, 14, 15 showed cytotoxic effects. The IC50 values (μM) of compound 14 (41.87, 51.98) were about equal to caffeic acid phenethyl ester’s (34.60, 42.26). Structure-activity relationship analysis demonstrated that the a, b-unsaturated double bond and the phenolic hydroxyl group in caffeic acid phenethyl ester were essential for the antitumor activities. Besides, the cytotoxic properties of these compounds were determined by the methoxy groups on the phenyl ring and the location of aromatic hydroxyl groups. These results may be of great benefit to people in screening new anticancer drug candidates.